Traditional Economic Space Management System in Pasar Raya Padang, West Sumatera Post-Earthquake 2009 - Zusmelia Zusmelia; Firdaus Firdaus (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2016)
The Pasar Raya Padang suffered various dynamics and changes since the West Sumatera earthquake 2009. Many studies had been conducted by academicians and researchers, but no study offering the model of economic space govern at Pasar Raya Padang according to traders’ needs. This paper was conducted by qualitative approach offers the models of traditional economic space govern in the city of Padang. This research had been conducted since 2015 in Pasar Raya Padang. The data were collected through in-depth interviews, focus group discussions (FGD), observation and document study. The result is that the traders as the primary market stakeholders want to have the model of economic space govern integrated over the system, the infrastructures, and market layout. The traders intend to have Pasar Raya Padang that still uses traditional system but the physical buildings that are set up as a modern market with complete facilities.